QUALITY OF EMPLOYMENT FROM A GEOGRAPHICAL PERSEPCTIVE. A SHOW CASE OF THE ROMANIAN DANUBE VALLEY - IRENA MOCANU (Revue Roumaine de Géographie)
The aim of this study is to analyse the territorial changes in terms of quality of employment in the urban and rural administrative units located along the Romanian Danube Valley during the period of transition, post-transition and of crisis. Using and adapting the methodological framework for measuring the quality of employment, the author selected statistical variables appropriate for constructing some statistical indicators and, finally, the index of quality of employment main characteristics. The study highlights some relevant aspects concerning the territorial changes in terms of quality of employment in the Romanian Danube Valley during the last two decades: the inverse correlation between the occupancy in agriculture and the level of quality of employment; very low and low levels of quality of employment widespread in the rural space and in the small Danubian towns, the quality of employment decline in the majority of the Romanian Danube Valley settlements.